Uniforme escolar infantil: seu posicionamento na identificação dos gêneros - Rabelo Andrade, Raquel (2013)
The school uniform is part of brazilian students routine since the midnineteenth century, and still remains a widely used device by both public and private schools. Therefore, some considerations and analysis could be made in relation to the representation and identification of the genera in uniform in order to examine their contribution in the constitution of gender identities. Thus, this study identifies, through a literature search and by an analysis of images, the relationship established between the identification of child gender and school uniforms since its advent to the present.